Comparison between CHADS2 and CHA2DS2‐VASc score in a stroke cohort with atrial fibrillation. Issue 4 (27th July 2012) - Giralt‐Steinhauer, E.; Cuadrado‐Godia, E.; Ois, Á.; Jiménez‐Conde, J.; Rodríguez‐Campello, A.; Soriano, C.; Roquer, J.
<x xml:space="preserve">Abstract</x> Background and purpose In patients with atrial fibrillation (AF), stroke risk stratification schemes have been developed to optimize antithrombotic treatment. The CHADS2 score is frequently used but has limitations. The CHA2DS2‐VASc score improves risk prediction. Our objectives are to describe CHADS2 and CHA2DS2‐VASc score distribution in a cohort of patients with AF and first‐ever ischaemic stroke (FIS) and to identify differences in embolic risk stratification. Methods Our cohort included 589 patients with FIS, previous modified Rankin score ≤ 3, and non‐valvular AF. We recorded demographic data, vascular risk factors, and antithrombotic pre‐treatment. The CHADS2 and CHA2DS2‐VASc scores were calculated according to clinical status before stroke onset. Results In 186 (31.6%) patients, AF was previously unknown. Of patients with known AF and CHADS2 ≥2 (n = 320), only 103 (32.2%) were taking anticoagulants; more than half of these patients had an INR <2. The CHADS2 score placed 142 (24.1%) patients in the low–intermediate risk (score ≤ 1) category compared with 21 (3.6%) with CHA2DS2‐VASc, P < 0.001. Applying CHA2DS2‐VASc reclassified 121 (85.2%) subjects in the CHADS2 low–intermediate risk category as high risk (≥2), an indication for anticoagulants. Of the 21 patients who suffered a stroke despite their low CHA2DS2‐VASc score (≤1), seven (33.3%) reported alcohol overuse, and six (28.5%) had a concomitant stroke etiology. Conclusions About 25% of FIS patients with AF had a CHADS2 score ≤ 1. Despite the high CHADS2 score of our population, few patients received the recommended antithrombotic treatment according to their thromboembolic risk. Using the CHA2DS2‐VASc schema significantly increased the percentage of patients indicated for anticoagulation.